Constructing Meaning in the Song Lyrics “Beyond” in Moana 2: A Semiotic Analysis - Fissilmi, Annisa; Zuhroni; Syamsurrijal (Jurnal Ilmu Sosial dan Humaniora, 2025)
Songs are a unique form of art that combines poetic language and melody to express deep meanings. This study examines the song Beyond from Disney’s Moana 2, focusing on its construction of meaning through Roland Barthes’ semiotic theory. The analysis explores the denotative, connotative, and mythological meanings of the lyrics. The song portrays themes of self-discovery, cultural identity, and the hero’s journey, with lyrics that serve as a narrative focal point in the film. A qualitative descriptive approach is employed in this research to uncover the explicit meanings in the lyrics, such as Moana’s journey into uncharted seas, while uncovering emotional aspects like her internal struggle between personal aspirations and familial responsibilities. Findings reveal that Beyond associates personal growth with cultural narratives that reflect universal human struggles, such as balancing individual aspirations with also collective responsibilities. Moana’s journey reflects the balance between honoring cultural heritage and pursuing individual purpose, which resonates with audiences of diverse backgrounds. This research demonstrates how animated musical content can communicate deep cultural messages and universal truths through layered semiotic meanings, making complex themes accessible to a broad audience